JPTCP 2023
DOI: 10.47750/jptcp.2023.30.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of quinolones resistant Salmonella typhi isolates from patients infected with Typhoid fever in Al-Najaf province, Iraq

Abstract: Background: The global spread of typhoid fever is still a major public health concern. Typhoid fever is a potentially fatal infection often treated with quinolones, especially fluoroquinolones. Resistance to quinolones antibiotics in Salmonella typhi has made it harder to treat and has led to more mortalities. In this study, we detected of the qnr genes (plasmid-mediated quinolone resistance PMQR) in S.typhi isolated from patients in two main hospitals in AL-Najaf province, Iraq and determined the clonal relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 47 publications
0
0
0
Order By: Relevance
“…"The occurrence of S. typhi from stool of patients in relationship to their age was higher at age 21-30 years, and this is in agreement with a study which reported high occurrence of S. typhi in patients of age > 10-41 years [17] and 21-31 years" [21].…”
Section: Molecular Detection Of Plasmid Mediated Quinolone Resistant ...supporting
confidence: 88%
See 1 more Smart Citation
“…"The occurrence of S. typhi from stool of patients in relationship to their age was higher at age 21-30 years, and this is in agreement with a study which reported high occurrence of S. typhi in patients of age > 10-41 years [17] and 21-31 years" [21].…”
Section: Molecular Detection Of Plasmid Mediated Quinolone Resistant ...supporting
confidence: 88%
“…It is one of the leading causes of death and infections in developing nations, and also a frequent cause illnesses in Africa, particularly Nigeria. A study by Jubair et al in Iraq [17], stated a low prevalence of the S.typhi strain in Iraq (13%). This isn't consistent with another study by Rahman et al [18] where other Middle Eastern countries had an 80.0% of S.typhiinfected patients, suggesting that most S. typhi infections originate from the Asian continent, while the remainder is primarily from Africa and Latin America [18].…”
Section: Molecular Detection Of Plasmid Mediated Quinolone Resistant ...mentioning
confidence: 97%